Important IICA experiences which contribute to sustainable agricultural development in Guyana&profiles/curriculum vitae of Guytca professional staff - Instituto Interamericano de Cooperación para la Agricultura (IICA) (IICA, 2020)
This project aims to support the development of an effective rural development strategy through the promotion and implementation of productive activities which build capacity and improve incomes in participating rural communities.